2017
DOI: 10.1177/1087057116681726
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Investigation of the Best Buffers for Use in Screening by MALDI–Mass Spectrometry

Abstract: Matrix-assisted laser desorption/ionization-mass spectrometry (MALDI-MS) offers a label-free alternative for the screening of biochemical targets in both 1536- and 6144-assay formats, as well as potentially providing increased sensitivity, reproducibility, and the simultaneous detection of multiple assay components within a specified m/z range. Ion suppression effects are one of the principal limitations reported for MS analysis. Within MALDI-MS screening, it has been identified that certain biochemical compon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
38
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(39 citation statements)
references
References 7 publications
1
38
0
Order By: Relevance
“… 26 We therefore modified established kinase assay buffers to be more compatible with MALDI TOF, guided by a recent investigation into MALDI-MS–friendly buffers. 19 Initial experiments in the ADP Hunter assay showed that the removal of NaCl from the assay buffer did reduce the signal window but did not alter the rank order of inhibitors. We therefore removed NaCl from the assay buffer of the MALDI assay.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“… 26 We therefore modified established kinase assay buffers to be more compatible with MALDI TOF, guided by a recent investigation into MALDI-MS–friendly buffers. 19 Initial experiments in the ADP Hunter assay showed that the removal of NaCl from the assay buffer did reduce the signal window but did not alter the rank order of inhibitors. We therefore removed NaCl from the assay buffer of the MALDI assay.…”
Section: Resultsmentioning
confidence: 99%
“…Recent developments based on electrospray ionization (ESI) such as RapidFire 15 , 16 or acoustic loading of the mass spectrometer 17 have substantially improved the throughput in mass spectrometry–based label-free systems, but ESI suffers from the need to clean up samples due to the low tolerance for salts and other compounds. Matrix-assisted laser desorption/ionization (MALDI) 18 mass spectrometry, on the other hand, is tolerant to a number of standard buffer components 19 and has rapidly become more popular in the field of drug discovery due to requiring very small sample quantities, minimal sample cleanup, and, most important for high-throughput screening (HTS), very high speed. Historically, MALDI is the most validated and robust surface ionization method whereby the analyte is mixed with a matrix, typically low molecular weight organic acids, and then co-crystalized on a metal target.…”
Section: Introductionmentioning
confidence: 99%
“…Suppression of ionization is one of the biggest challenges in MALDI-MS sample preparation. 11,16 Since we expected such ionization problems with our established c-MET assay buffer, we turned our attention to the adjustment of buffer ingredients and tested the c-MET kinase assay performance with those different buffer conditions. To be functional in an in vitro setting, biological systems require a certain pH range and are dependent on salts and/or certain metal cations for their activity.…”
Section: Resultsmentioning
confidence: 99%
“…Addressing those challenges has been a major focus of the HTS field. 3,11,12,15 The launch of Bruker's RapifleX MALDI Pharma Pulse (Bremen, Germany) has given the field a boost in measurement speed and throughput, which enables analysis of about 600,000 to 1 million compounds per week on a single platform. This single platform contains an integrated MALDI-MS system as a "in-line reader" and all other equipment for highthroughput applications, like compound addition and incubation (Suppl.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3] Although conventionally considered a low-throughput technology, recent advances in MS and liquid handling technologies and liquid handling tools have enabled MALDI TOF MS to emerge as a powerful tool for label-free high-throughput screening (HTS) within both the pharmaceutical industry and academic sphere. [4][5][6] This platform has been already well established for in vitro assays to monitor post-translational modifications such as ubiquitylation, 7,8 phosphorylation 9,10 and methylation, 11,12 as the read-out is relatively simple with often just a single substrate and product. Similar to MALDI, laser desorption ionisation can also be combined with self-assembled monolayers (SAMs), also known as SAMDI.…”
Section: Introductionmentioning
confidence: 99%